Slinky Malinki, open the door - Dodd, Lynley (Berkeley, Calif. : Tricycle Press, 2006)
Slinky Malinki, a mischievous cat, and Stickybeak Syd, a bird, get into lots of trouble when they are left alone in the house.
3.0
K-3.
K-3
Keywords: Birds -- Juvenile fiction; Cats -- Juvenile fiction; Birds -- Fiction; Cats -- Fiction; Stories in rhyme; Birds -- Fiction; Cats -- Fiction; Stories in rhyme